Inhibitory control in euthymic bipolar disorder: Event related potentials during a Go/NoGo task. Issue 4 (April 2017) - Morsel, A.M.; Dhar, M.; Hulstijn, W.; Temmerman, A.; Morrens, M.; Sabbe, B.
Highlights: Reduced NoGo N2 amplitudes in bipolar disorder reflect abnormalities in early stages of inhibition. Patients with bipolar disorder (BD) have increased NoGo P3 amplitudes together with normal inhibitory behavior. Patients with BD seem to compensate for abnormal early inhibition with increased cortical activity. Abstract: Objectives: Patients with bipolar disorder (BD) are reported to have difficulties with inhibition, even in a euthymic state. However, the literature on cortical activity associated with response inhibition in BD remains ambiguous. This study investigates inhibition in euthymic BD using electrophysiological measures, while controlling for effects of specific medications. Methods: Twenty patients with BD were compared with eighteen healthy controls on a Go/NoGo task while electroencephalogram was recorded. Behavioral and event-related potential (ERP) measurements were analyzed for the two groups. Medication effects were controlled for in the analysis. Results: Patients with BD had marginally reduced NoGo N2 amplitudes and increased NoGo P3 amplitudes compared with healthy controls when patients using benzodiazepines were excluded from the study. No behavioral differences between the groups were found. Conclusions: Reduced NoGo N2 amplitudes in BD reflect aberrant conflict detection, an early stage of the inhibition process. In addition, increased NoGo P3 amplitudes in BD despite normal task performance reflect an overactive cortical system during a simple inhibition task. Significance: Difficulties in early stages of inhibition in BD appear to have been compensated by increased cortical activation. This study extends current knowledge regarding cortical activations relating to inhibition in BD.